Maternal social support and health facility delivery in Southwest Ethiopia - Abebe Mamo; Muluemebet Abera; Lakew Abebe; Nicole Bergen; Shifera Asfaw; Gebeyehu Bulcha; Yisalemush Asefa; Endale Erko; Kunuz Haji Bedru; Mihiretu Lakew; Jaameeta Kurji; Manisha A. Kulkarni; et al. (BMC, 2022)
Abstract Background Maternal mortality continues to decrease in the world but remain the most important health problems in low-income countries. Although evidence indicates that social support is an important factor influencing health facility delivery, it has not been extensively studied in Ethiopia. Therefore, this study aimed to assess the effect of maternal social support and related factors on health facility delivery in southwest Ethiopia. Methods A cross-sectional survey data on 3304 women aged 15-47 years in three districts of Ethiopia, were analyzed. Using multivariable logistic regression, we assessed the association between health facility birth, social support, and socio-demography variables. Adjusted odds ratios with 95% confidence intervals were used to identify statistically significant associations at 5% alpha level. Result Overall, 46.9% of women delivered at health facility in their last pregnancy. Average travel time from closest health facility (AOR: 1.51, 95% CI 1.21 to 2.90), mean perception score of health facility use (AOR: 1.83, 95% CI 1.44 to 2.33), involvement in final decision to identify their place of childbirth (AOR: 2.12, 95% CI 1.73 to 2.58) had significantly higher odds of health facility childbirth. From social support variables, women who perceived there were family members and husband to help them during childbirth (AOR: 3.62, 95% CI 2.74 to 4.79), women who received continuous support (AOR: 1.97, 95% CI 1.20 to 3.23), women with companions for facility visits (AOR: 1.63, 95% CI 1.34 to 2.00) and women who received support from friends (AOR: 1.62, 95% CI 1.16 to 3.23) had significantly higher odds of health facility childbirth. Conclusions Social support was critical to enhance health facility delivery, especially if women's close ties help facility delivery. An intervention to increase facility delivery uptake should target not only the women's general social supports, but also continuous support during childbirth from close ties including family members and close friends as these are influential in place of childbirth. Also actions that increase women's healthcare decision could be effective in improving health facility delivery.